Describing ourselves Wittgenstein and autobiographical consciousness - Hagberg, Garry, 1952- (Oxford : Clarendon, 2008)
Garry Hagberg presents a philosophical investigation of self-description. He explores the profound implications that Wittgenstein's later work has for our understanding of the human condition, and offers philosophical interpretations of a fascinating range of autobiographical writings.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Wittgenstein, Ludwig, -- 1889-1951.; Self (Philosophy); Autobiography